Singlet Oxygen Quenching Effect of Quercetin in Erythrosine-Sensitized Photooxidation of Oil-in-Water Emulsion - Posman Sibuea; Umar Santoso; Zuheid Noor; Sri Raharjo (Indonesian Food and Nutrition Progress, 2004)
Oxidation reaction can be initiated by either diradical triplet oxygen or non radical singlet oxygen. The singlet oxygen can be formed infoods from triplet oxygen by photosensitized reaction. This research was intended to study the quenching effect of quercetin on lipid oxidation rate in the erythrosine-sensitized photooxidation of oil-in-water emulsion. Palm oil-in-water emulsion, containing erythrosine 100 ppm and quercetin 0, 25, 50, 75 and 100 ppm, were prepared with polyoxyelhylene 100 stearyl ether (Brij 700) or polyoxyethylene sorbitan monolaurate (Tween 20). Structurally Brij 700 has 5 times longer polyoxyethylene groups than Tween 20. The mixture were stored under 4000 luxfluorescent light for 10 h and peroxide values were measured at 2 h interval. Erythrosine effectively sensitized the photooxidation of palm oil-in-water emulsion, as expected. Lipid oxidation rates, as determined by the formation of lipid hydroperoxides and headspace oxygen, in palm oil-in-water emulsions containing erythrosine decreased with increasing quercetin concentration. At pH 3, the peroxide value was higher than at pH 7. Brij 700 decreased production of lipid hydroperoxides from palm oil-in-water-emulsions compared to emulsions stabilized by Tween 20. The results indicate that quercetin is an efective singlet oxygen quencher in palm oil-in-water emulsion and the surfactant headgroup size could be an important determinant in the oxidative stability of food emulsions.